Self-Efficacy, Meaning of Work as Vocation, and Work Engagement of High School Teachers in Surabaya - Adi Satria Indramawan (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
A teacher with self-efficacy is more able to accomplish any task from the management so that he is engaged to his work, and a teacher who regards his work as a calling has the proper motivation to work better. The aim of this study was to find whether there is a correlation between teacher’s self-efficacy and work engangement and whether there is a correlation between the meaning of work as a calling and work engagement of private high school teachers in Surabaya. The subjects (N = 87) were teachers from three private schools in Surabaya. The data was collected through close-ended statements scales with five options of answer that were later analyzed through a nonparametric correlation test with SPSS 19.00. The result showed a correlation between teachers’ self-efficacy and work engagement (r = .08; p < .05) and a correlation between the meaning of work as a calling and work engagement (r = .612; p < .05). Based on the result, it could be concluded that teachers’ self efficacy and meaning of work as a calling could not be treated as one unit, but each correlated independently with their work engagement.